Online Versus Offline Price Expectations of Indian Consumers - Nargundkar, Rajendra; Manoharan, Sivaraman (Journal of Contemporary Research in Management (JCRM), 2017)
The issue of online versus offline pricing is very pertinent in India, where e-commerce sites like Flipkart and Amazon are growing rapidly at the expense of some offline stores. This study examines what consumers expect in terms of prices online and offline for a wide variety of goods. The sample of 125 executives were given a questionnaire that fixed an offline product and asked them what price they would pay online for the same. Across a variety of products, consumers were very clear that they would pay less online. Â  The results have implications for pure-play offline retailers who need to add value to their offerings to remain competitive, and also for the retailers who want to offer multiple channel options to consumers. They have to adopt a pricing strategy which will keep consumer expectations of differential (mostly lower) online prices in mind. Â  Keywords: Online, Offline, Pricing, Expectations, Omni-channel,